2012
DOI: 10.1063/1.4755750
|View full text |Cite
|
Sign up to set email alerts
|

A computational investigation of the phase behavior and capillary sublimation of water confined between nanoscale hydrophobic plates

Abstract: Thin films of water under nanoscopic confinement are prevalent in natural and manufactured materials. To investigate the equilibrium and dynamic behavior of water in such environments, we perform molecular dynamics simulations of water confined between atomistically detailed hydrophobic plates at T = 298 K for pressures (-0.1) ≤ P ≤ 1.0 GPa and plate separations of 0.40 ≤ d ≤ 0.80 nm. From these simulations, we construct an expanded P-d phase diagram for confined water, and identify and characterize a previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
41
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 122 publications
4
41
1
Order By: Relevance
“…The observation of a flat square structure is consistent with the recent experimental observation. However, the sequence of low energy phases identified differs significantly from that predicted in force field based studies [13,14,19,21,23] and a recent DFT report [26]. Interestingly the sequence of structures observed depends sensitively on the confinement width used, suggesting that it should be possible to tune the monolayer ice structures produced in experiments by e.g.…”
contrasting
confidence: 59%
See 1 more Smart Citation
“…The observation of a flat square structure is consistent with the recent experimental observation. However, the sequence of low energy phases identified differs significantly from that predicted in force field based studies [13,14,19,21,23] and a recent DFT report [26]. Interestingly the sequence of structures observed depends sensitively on the confinement width used, suggesting that it should be possible to tune the monolayer ice structures produced in experiments by e.g.…”
contrasting
confidence: 59%
“…Given that bulk ice I is built from hexagonal layers and double layer hexagonal structures have been observed frequently in force field simulations [16][17][18], it is not surprising that a low enthalpy hexagonal structure should be identified. However monolayer hexagonal ice has yet to be observed experimentally and in force field simulations it has only been found when an hexagonally patterned substrate has been used as a template [21].…”
mentioning
confidence: 99%
“…Drying or cavitation to a vapor phase results in a strong attractive force that can promote the aggregation of the confining objects. 12,31 Surface-induced drying transitions have been observed and characterized in numerous simulations of idealized [37][38][39][40][41][42][43][44][45][46][47][48][49] and biologically relevant systems [18][19][20][50][51][52][53][54] and have also been invoked to interpret the long-range hydrophobic attraction. [55][56][57][58][59][60] Macroscopic thermodynamic arguments can predict this drying transition, and the model system often invoked is that of two rigid parallel L × L plate-like solutes, separated by a distance D, and immersed in a bath of water at a fixed chemical potential μ and temperature T. 43,61 We consider the control volume to be a L × L × (D + ε) rectangular box, where ε is an arbitrarily small length that allows inclusion of the interface between the plates and the surrounding bulk fluid yet excludes any bulk fluid itself.…”
Section: Introductionmentioning
confidence: 99%
“…This cutoff distance has been used by us (15,17) and is very close to the 9 Å used by Stanley and coworkers (23,36). Other groups have used the Ewald sum method to treat the long-range charge-charge interaction (20,37). Previously, we have shown that when computing the melting point of bulk ice I h (e.g., based on the TIP5P model with the two-phase coexistence method), the Ewald sum method tends to give a lower melting point compared with the simple truncation method (33).…”
Section: Methodsmentioning
confidence: 99%